The Influence of Entrepreneurial Characteristics and Digital Maturity on the Resilience of Micro, Small, and Medium Enterprises in Bandar Lampung, Indonesia - Revando Bennedic Agusriyanto; Ayi Ahadiat; Nuzul Inas Nabila (STIE Amkop Makassar, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia’s economy; however, their resilience often faces numerous challenges. This study aims to analyze the influence of entrepreneurial characteristics and digital maturity on MSME resilience in Bandar Lampung. Using a quantitative approach, data were collected from 100 MSME owners through questionnaires and analyzed using multiple linear regression. The findings reveal that entrepreneurial characteristics positively influence business resilience, with a regression coefficient of 0.137 and a significance level of 0.061. Meanwhile, digital maturity has a more significant impact, with a regression coefficient of 0.729 and a significance level of 0.000. The R Square value of 0.668 indicates that 66.8% of the variation in business resilience can be explained by these two variables. These findings confirm that digital maturity plays a more dominant role than entrepreneurial characteristics in enhancing MSME resilience. Therefore, MSME owners are encouraged to adopt digital technology to strengthen their competitiveness and business resilience.